The effect of acupuncture on blood glucose control in patients with type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials - Si, Yuqi; Chen, Jiayao; Chen, Lizhu; Zheng, Yan; Qiu, Yixuan; Wang, Beibei; Liang, Yiwen; Zhang, Yubo; Chen, Yaling (Frontiers in Endocrinology, 2025)
PurposeThis meta-analysis aimed to ascertain the effectiveness of acupuncture in treating clinical symptoms of type 2 diabetes mellitus (T2DM) and to summarize the acupoints and meridians involved.MethodsPubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang were thoroughly retrieved to acquire randomized controlled trials (RCTs) evaluating acupuncture as an adjunct treatment for T2DM. Outcome measures focused on improvements in T2DM clinical symptoms. The meta-analysis was implemented leveraging RevMan 5.4 and Stata 15 software, with sensitivity and subgroup analyses to assess the stability of results and identify heterogeneity sources.Results21 RCTs encompassing 2,117 individuals with T2DM were analyzed. The results of 2-hour postprandial glucose (2h PG), body mass index (BMI), fasting blood glucose (FBG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), bilateral median nerve motor conduction velocity, and plasma viscosity were reliable. No publication bias was noted, except for Packed Cell Volume (PCV) and Traditional Chinese Medicine Syndrome Score Scale (TCMSS). The meta-analysis showed that acupuncture significantly improved clinical markers such as glycated hemoglobin A1c (HbA1c), 2h PG, FBG, and fasting serum insulin (FINS). Subgroup analysis for FBG, 2h PG, and triglycerides (TG) indicated that the primary source of heterogeneity for FBG was related to participants with uncomplicated T2DM and a treatment duration of less than three months. No significant heterogeneity was observed for 2h PG, while the TG data were unstable.ConclusionAcupuncture can significantly alleviate the main clinical symptoms of T2DM, but significant heterogeneity was observed for individual indicators. Further investigation is needed to corroborate its precise therapeutic effectiveness and identify potential influencing factors.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024602165, identifier CRD42024602165.